Method for reusing active material using scrap cathodes
A method for recycling positive electrode active materials from lithium secondary batteries through heat treatment, washing, and surface coating addresses the inefficiencies of existing methods, enabling environmentally friendly and cost-effective reuse with maintained performance.
Patent Information
- Application Number
- JP2023543194
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-08-02
- Filing Date
- 2022-08-01
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-08-01
AI Technical Summary
Existing methods for recycling positive electrode active materials from lithium secondary batteries are environmentally unfriendly, costly, and inefficient, particularly due to the use of acids for extraction and the inability to recover lithium, and they do not effectively utilize positive electrode scraps generated during manufacturing.
A method involving heat treatment to separate the current collector from the active material layer, followed by washing with a lithium compound solution, adding a lithium precursor, annealing, and surface coating to recover and reuse the active material without dissolving it, thus avoiding the use of toxic solvents and complex processes.
The method allows for the environmentally friendly and economical reuse of positive electrode active materials, maintaining excellent resistance and capacitance characteristics, and is suitable for mass production, with the recovered materials achieving performance comparable to fresh active materials.
Smart Images

Figure 0007612880000007 
Figure 0007612880000008 
Figure 0007612880000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for recycling resources during the manufacture of a lithium secondary battery. In particular, the present invention relates to a method for recovering and reusing positive electrode scrap generated in the manufacturing process of a lithium secondary battery or a positive electrode active material of a lithium secondary battery that is discarded after use. This application claims priority to Korean Patent Application No. 10-2021-0101580 filed on August 2, 2021, and the contents disclosed in the specification and drawings of the application are incorporated herein in their entirety. [Background technology]
[0002] Lithium secondary batteries, which can be repeatedly charged and discharged, have been attracting attention as an alternative to fossil energy. Lithium secondary batteries have been mainly used in traditional handheld devices such as mobile phones, video cameras, and power tools. However, in recent years, the application of lithium secondary batteries has gradually expanded to electrically driven automobiles (EV, HEV, PHEV), large-capacity energy storage systems (ESS), uninterruptible power supplies (UPS), etc.
[0003] A lithium secondary battery includes an electrode assembly in which unit cells are assembled, each having a structure in which a positive electrode plate and a negative electrode plate, each having an active material coated on a current collector, are arranged with a separator sandwiched therebetween, and an exterior material, i.e., a battery case, which seals and houses the electrode assembly together with an electrolyte. A lithium-based oxide is mainly used as the positive electrode active material of a lithium secondary battery, and a carbon material is used as the negative electrode active material. The lithium-based oxide contains metals such as cobalt, nickel, and manganese. In particular, cobalt, nickel, and manganese are very expensive valuable metals, and among them, cobalt belongs to the strategic metals, and countries around the world are particularly interested in supply and demand. The number of cobalt-producing countries is also limited, so that it is known as a metal with unstable supply and demand around the world. If the supply and demand balance of strategic metal raw materials is disrupted, there is a high possibility that raw material prices will rise.
[0004] Research has been conducted on the recovery and recycling of such valuable metals from lithium secondary batteries (waste batteries) that are discarded after their lifespan has expired. In addition to waste batteries, it would be more preferable if resources could be recovered from waste discarded after punching out positive electrodes or from positive electrodes that have become defective during the process.
[0005] Currently, in the manufacture of lithium secondary batteries, as shown in Fig. 1, a long sheet-like positive electrode collector 10 such as an aluminum (Al) foil is coated with a positive electrode slurry, which is a mixture of a positive electrode active material, a conductive material, a binder, a solvent, etc., to form a positive electrode active material layer 20, thereby manufacturing a positive electrode sheet 30, and then a positive electrode plate 40 is punched out to a predetermined size. The remaining portion after punching is discarded as positive electrode scrap 50. If the positive electrode active material could be recovered from the positive electrode scrap 50 and reused, this would be very desirable from the industrial, economic, and environmental viewpoints.
[0006] In most conventional methods for recovering positive electrode active materials, the positive electrode is dissolved with hydrochloric acid, sulfuric acid, nitric acid, etc., and then the active material elements such as cobalt, nickel, and manganese are extracted and used again as raw materials for the synthesis of positive electrode active materials. However, the method for extracting active material elements using acids has the disadvantages that the process for recovering pure raw materials is not environmentally friendly, and the process costs increase because a neutralization process and a wastewater treatment process are required. In addition, it has the disadvantage that lithium, one of the main elements of positive electrode active materials, cannot be recovered. To overcome these disadvantages, a method is needed that does not dissolve the positive electrode active material and allows the active material to be directly reused without extracting it in elemental form. Summary of the Invention [Problem to be solved by the invention]
[0007] The problem to be solved by the present invention is to provide a method for recovering and reusing active material from positive electrode scraps. [Means for solving the problem]
[0008] In order to solve the above problems, the method for reusing a positive electrode active material of the present invention includes the steps of: heat-treating positive electrode scrap including a positive electrode active material layer of a lithium composite transition metal oxide including nickel, cobalt, and manganese or aluminum on a current collector to thermally decompose a binder and a conductive material in the positive electrode active material layer, thereby separating the current collector from the positive electrode active material layer and recovering an active material in the positive electrode active material layer; primarily washing the recovered active material with an aqueous solution of a lithium compound that is basic in an aqueous solution state; adding a lithium precursor to the washed active material and annealing it; secondarily washing the annealed active material; and surface-coating the secondarily washed active material to obtain a reusable active material.
[0009] The heat treatment can be carried out at 300 to 650° C. in air or in an oxygen atmosphere.
[0010] The heat treatment may be carried out at 550° C. for 30 minutes with a heating rate of 5° C. / min.
[0011] The lithium compound aqueous solution is prepared to contain more than 0% and not more than 15% of the lithium compound, and preferably uses LiOH. The first cleaning can be performed within 1 hour.
[0012] The primary washing can be performed by immersing the recovered active material in the aqueous lithium compound solution and stirring the solution.
[0013] The lithium precursor can be any one or more of LiOH, Li2CO3, LiNO3, and Li2O.
[0014] The lithium precursor may be added in an amount sufficient to compensate for the proportion of lost lithium relative to the proportion of lithium and other metals in the raw active material used in the positive electrode active material layer.
[0015] For example, the lithium precursor may be added so that the amount of lithium added is 0.001 to 0.4 molar ratio.
[0016] Furthermore, preferably, the lithium precursor can be added so that the amount of lithium further added is 0.0001 to 0.1 molar ratio based on the molar ratio of lithium:other metal=1:1.
[0017] The annealing may be carried out at 400 to 1000° C. in air or an oxygen atmosphere.
[0018] The temperature of the annealing step may be above the melting point of the lithium precursor.
[0019] The active material in the active material layer is recovered in a powder form, and carbon components resulting from carbonization of the binder and conductive material may not remain on the surface.
[0020] The surface coating step may be performed by coating the surface with at least one of a metal, an organometallic, and a carbon component in a solid or liquid phase manner, followed by heat treatment at 100 to 1200°C.
[0021] The content of the nickel may be 60 mol % or more based on the total number of moles of the transition metals.
[0022] The content of the nickel may be 80 mol % or more based on the total number of moles of the transition metals.
[0023] The reusable active material may have a fluorine (F) content of 100 ppm or less.
[0024] In the present invention, after the first washing step, the method may further include a step of mixing the first washed active material with a lithium precursor solution and spray drying the mixture. Effect of the Invention
[0025] According to the present invention, waste positive electrode active materials such as positive electrode scraps generated in the manufacturing process of lithium secondary batteries can be reused without using acid, which is environmentally friendly. According to the method of the present invention, since a neutralization step and a wastewater treatment step are not required, environmental problems can be alleviated and process costs can be reduced.
[0026] According to the present invention, the positive electrode active material can be recovered without the metal elements becoming unrecoverable. The current collector can also be recovered because it does not dissolve. This method is economical because it is not a method in which active material elements are extracted and used again as raw materials for synthesizing a positive electrode active material, but a method in which the active material recovered in powder form can be directly reused.
[0027] According to the present invention, since no toxic or explosive solvents such as NMP (N-methylpyrrolidone), DMC (dimethyl carbonate), acetone, or methanol are used, the process is safe, and since simple processes such as heat treatment, washing, and annealing are used, the process control is easy and it is suitable for mass production.
[0028] According to the present invention, excellent resistance and capacity characteristics can be achieved without deteriorating the electrochemical performance of the recovered active material.
[0029] In particular, the present invention can be effectively applied to a method for reusing a high-content Ni-based (Ni-rich) positive electrode active material, and the characteristics of the reused active material can be restored or improved to 99% or more compared to a fresh active material that has never been used.
[0030] The following drawings attached to this specification are illustrative of embodiments of the present invention, and serve to further understand the technical concept of the present invention together with the detailed description of the invention described below. Therefore, the present invention should not be interpreted as being limited only to the matters depicted in such drawings. [Brief description of the drawings]
[0031] [Figure 1]FIG. 13 is a diagram showing positive electrode scraps that are discarded after positive electrode plates are punched out from the positive electrode sheet. [Diagram 2] 2 is a flow chart of a method for reusing active materials according to one embodiment of the present invention. [Diagram 3] 1 is a SEM photograph of Sample 1, which is a fresh active material. [Figure 4] 1 is a SEM photograph of Sample 3 to which some steps of the method according to the present invention are applied. [Diagram 5] 1 is a particle size distribution graph of the active materials of Samples 1 and 3. [Figure 6] 1 is a particle size distribution graph of the active materials of Samples 1, 4, 5 and 6. [Figure 7] 1 is a graph showing the results of cell evaluation using sample active materials, showing capacity versus cycle number. [Figure 8] 1 is a graph showing the results of cell evaluation using sample active materials, showing capacity versus cycle number. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0032] Hereinafter, a preferred embodiment of the present invention will be described in detail with reference to the accompanying drawings. Prior to this, the terms and words used in this specification and claims are not to be construed as being limited to their ordinary or dictionary meanings, but are to be construed as being in accordance with the meaning and concept of the technical idea of the present invention, in accordance with the principle that the inventor himself can appropriately define the concept of the term in order to best describe the invention. Therefore, it should be understood that the embodiment described in this specification and the configuration shown in the drawings are merely the most preferred embodiment of the present invention, and do not represent the entire technical idea of the present invention, and therefore there may be various equivalents and modifications that can be substituted therefor at the time of this application.
[0033] In the following description, reference is made to the accompanying drawings, which form a part of this application. The embodiments described in the detailed description, the drawings, and the claims are not limiting. Other embodiments may be utilized, and other changes may be made, without departing from the spirit and scope of the subject matter disclosed herein. It will be understood that the aspects of the invention as generally described herein and illustrated by the drawings may be arranged, substituted, combined, separated, and designed in a variety of other configurations, all of which are expressly contemplated herein.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by a person of ordinary skill in the art to which this invention belongs (hereinafter referred to as "person of ordinary skill in the art").
[0035] The present invention is not limited by the specific embodiments described herein. As will be apparent to those skilled in the art, various changes and modifications can be made without departing from the spirit and scope of the present invention. In addition to those enumerated herein, functionally equivalent methods within the scope of the present application will be apparent to those skilled in the art from the above description. Such changes and modifications are within the scope of the appended claims. The present invention is limited only by the claims, along with the full scope of equivalents defined by such claims. It is to be understood that the present invention is not limited to the specific manner in which it may, of course, be varied. It is also to be understood that the terminology used herein is used only for the purpose of describing specific embodiments, and is not intended to be limiting.
[0036] In the case of the conventional active material recycling process, the main task was to extract valuable metals (nickel, cobalt, manganese, etc.) as elements from the active material of a lithium secondary battery whose performance has deteriorated after use, and resynthesize the active material. However, the present invention is different in that it recovers active material from cathode scraps generated during the manufacturing process of a lithium secondary battery.
[0037] In addition, in the case of known active material recycling processes, valuable metals are extracted using acid / base dissolution or reduction / melting with additives, and then chemical methods such as manufacturing them as metals (direct reduction method) or resynthesizing active materials are added, which further increases the process complexity and economic costs. However, the present invention relates to a method for directly reusing the positive electrode active material without dissolving it.
[0038] To directly reuse the positive electrode active material, a method is needed to remove the current collector from the positive electrode, which can be done by high-temperature heat treatment to remove the binder, by using a solvent to dissolve the binder, by dissolving the current collector itself, or by dry grinding and sieving to separate the active material.
[0039] When using a solvent to dissolve the binder, the stability of the solvent is important. NMP is the most efficient solvent, but it has the disadvantages of toxicity and high cost. Another disadvantage is that a solvent recovery process, such as reprocessing the waste solvent, is required. Dissolving the current collector is less expensive than using a solvent. However, it is difficult to remove foreign matter from the surface of the reused active material, and hydrogen gas is generated during the removal of the current collector, which may cause an explosion. It is difficult to completely separate the current collector and active material using dry grinding and sieving. The particle size distribution of the active material changes during the grinding process, making it difficult to remove the binder, which has the disadvantage of deteriorating the battery characteristics when it is reused.
[0040] In the present invention, the active material and the current collector are separated using a high-temperature heat treatment. In the present invention, the active material and the current collector are separated using a high-temperature heat treatment. Since this is a relatively simple process that requires only heating, it is advantageous for mass production and commercialization. However, foreign matter must not remain on the surface of the reused active material. In the present invention, a step of removing foreign matter from the surface of the reused active material is also proposed.
[0041] Hereinafter, a method for reusing an active material according to an embodiment of the present invention will be described with reference to Fig. 2. Fig. 2 is a flow chart of a method for reusing an active material according to an embodiment of the present invention.
[0042] Referring to FIG. 2, first, cathode scraps to be discarded are prepared (step S10).
[0043] The positive electrode scraps may be the remaining portion after manufacturing a positive electrode sheet including a positive electrode active material layer on a current collector and punching it out as described above with reference to FIG. 1. Alternatively, the positive electrode scraps may be prepared by collecting positive electrodes that have become defective during the process. Alternatively, the positive electrode scraps may be prepared by separating positive electrodes from lithium secondary batteries that have been discarded after use.
[0044] For example, a slurry is prepared by mixing an active material, which is a lithium composite transition metal oxide (hereinafter, simply referred to as "NCM-based, NCA-based, or NCMA-based lithium composite transition metal oxide") containing nickel (Ni), cobalt (Co), and manganese (Mn) or aluminum (Al), carbon black, which is a carbon-based conductive material, and polyvinylidene fluoride (PVdF), which is a binder, with N-methylpyrrolidone (NMP), and coating the slurry on a sheet-type current collector made of aluminum foil. The slurry is then dried in a vacuum oven at about 120°C to prepare a positive electrode sheet, and a positive electrode plate of a certain size is punched out to prepare the remaining positive electrode scrap.
[0045] In particular, the present invention can be effectively applied to a method for reusing a high-content Ni-based (Ni-rich) positive electrode active material. For example, the nickel content may be 60 mol% or more based on the total moles of the transition metals. Furthermore, the nickel content may be 80 mol% or more based on the total moles of the transition metals.
[0046] Lithium composite transition metal oxides are used as the positive electrode active material of lithium secondary batteries, and among them, lithium cobalt oxide of LiCoO2, lithium manganese oxide (LiMnO2, LiMn2O4, etc.), lithium iron phosphate compound (LiFePO4, etc.), or lithium nickel oxide (LiNiO2, etc.) are mainly used. In addition, as a method to improve the low thermal stability of LiNiO2 while maintaining the excellent reversible capacity, nickel manganese-based lithium composite metal oxides in which part of nickel is replaced with manganese, which has excellent thermal stability, NCM-based lithium composite transition metal oxides in which nickel is replaced with manganese and cobalt, NCA-based lithium composite transition metal oxides in which nickel is replaced with cobalt and aluminum, and NCMA-based lithium composite transition metal oxides in which nickel is replaced with cobalt, manganese, and aluminum are used.
[0047] In this way, the positive electrode scrap has an active material layer on a metal foil current collector such as aluminum foil. The active material layer is formed by coating a slurry containing an active material, a conductive material, a binder, a solvent, etc., and therefore has a structure in which the binder connects the active material and the conductive material after the solvent evaporates. Therefore, the active material can be separated from the current collector by removing the binder.
[0048] Next, the cathode scrap is crushed to an appropriate size (step S20). Crushing refers to cutting or shredding the cathode scrap into pieces of an appropriate size that is easy to handle. After crushing, the cathode scrap is cut into pieces of, for example, 1 cm x 1 cm. For crushing, various dry grinding devices such as a hand mill, a pin mill, a disc mill, a cutting mill, and a hammer mill may be used, or a high-speed cutter may be used.
[0049] The crushing can be performed taking into consideration the handling of the cathode scrap and the required characteristics of the equipment used in the subsequent steps. For example, if an equipment requiring continuous processing for loading and unloading the cathode scrap is used, the cathode scrap must have good fluidity, so crushing of the cathode scrap that is too large is necessary. If the cathode scrap has an appropriate size, the crushing step S20 can be omitted.
[0050] Referring to FIG. 2, the positive electrode plate is heat-treated (step S30).
[0051] In the present invention, the heat treatment is carried out to thermally decompose the binder in the active material layer. The heat treatment can be performed at 300 to 650°C, and can therefore be called a high-temperature heat treatment. At temperatures below 300°C, it becomes difficult to remove the binder, and the current collector cannot be separated. At temperatures above 650°C, the current collector melts (Al melting point: 660°C), making it impossible to separate the current collector.
[0052] The heat treatment time is maintained to a degree that allows the binder to be sufficiently thermally decomposed. For example, it is about 30 minutes. It is preferably 30 minutes or more. The longer the heat treatment time, the longer the time for the binder to thermally decompose, but once it reaches a certain time, there is no difference in the thermal decomposition effect. Preferably, the heat treatment time is 30 minutes or more and 5 hours or less.
[0053] The heat treatment device may be any of various furnaces, for example, a box furnace, or, in consideration of productivity, a rotary kiln capable of continuous treatment.
[0054] After the heat treatment, the material may be cooled slowly or rapidly in air.
[0055] For example, the heat treatment may be performed at 550°C for 30 minutes at a heating rate of 5°C / min. The heating rate is, for example, a rate that can be reasonably implemented in a box furnace and that can heat the cathode scraps without causing thermal shock. 550°C is a temperature that allows the binder to be thermally decomposed well while taking into consideration the melting point of the Al current collector. At this temperature, heat treatment for less than 10 minutes is insufficient for thermal decomposition, so the heat treatment should be performed for 10 minutes or more, and preferably for 30 minutes or more.
[0056] The heat treatment causes the binder and conductive material in the active material layer to be pyrolyzed and removed as CO2 and H2O. As the binder is removed, the active material is separated from the current collector, and the active material to be recovered can be sorted into a powder form. Therefore, the current collector can be separated from the active material layer and the active material in the active material layer can be recovered by only step S30.
[0057] The heat treatment in step S30 may be performed in air or in an oxygen atmosphere. If the heat treatment is performed in a reducing gas or inert gas atmosphere, the binder and the conductive material are not thermally decomposed but are merely carbonized. If they are merely carbonized, carbon components remain on the surface of the active material, and the performance of the reusable active material decreases. If the heat treatment is performed in air, the carbon substances in the binder and the conductive material react with oxygen and are burned into CO and CO2 gas and removed, so that they are almost completely removed without remaining in the binder and the conductive material. Therefore, according to the present invention, the active material is recovered in a powder form, and the carbon components generated by the carbonization of the binder and the conductive material do not remain on the surface.
[0058] When a high-content Ni-based positive electrode active material is reused, it is preferable to perform the heat treatment in an oxygen atmosphere for Ni stability. O2 with a purity of 80% or more, preferably 90% or more, may be used.
[0059] Next, the recovered active material is subjected to a primary washing (step S40). In the primary washing, it is important to wash with an aqueous solution of a lithium compound that is alkaline in an aqueous solution state. Such an aqueous solution of a lithium compound is prepared to contain more than 0% and not more than 15% of a lithium compound, and preferably LiOH is used. The amount of LiOH is preferably 15% or less. If an excessive amount of LiOH is used, it may remain on the surface of the active material even after washing, which may affect the subsequent annealing process. In order to make the surface of the active material as clean as possible in the step before annealing, the addition of an excessive amount of LiOH is not good for the process, so it is limited to 15% or less.
[0060] The primary washing may be performed by immersing the recovered active material in such an aqueous lithium compound solution. The washing may be performed within one week, preferably within one day, more preferably within one hour after the immersion. If the washing is performed for more than one week, the lithium may be excessively dissolved, resulting in a decrease in capacity. Therefore, it is preferable to perform the washing within one hour. The primary washing includes immersing the active material in an aqueous lithium compound solution that is basic in the aqueous solution state, stirring the solution while the active material is immersed, and the like. It is preferable to perform stirring in parallel as much as possible. If the active material is only immersed in the aqueous lithium compound solution without stirring, the washing process will be slow, which may cause lithium to dissolve. Since the process time can be minimized by performing stirring in parallel, it is preferable to perform stirring at the same time as the impregnation with the aqueous lithium compound solution.
[0061] After the first wash, filtration can be followed by further drying in air in an oven (convection).
[0062] The reason for the primary cleaning using an aqueous solution of a lithium compound that is alkaline in the aqueous solution state is to remove LiF and metal fluorides that may be present on the surface of the recovered active material to modify the surface. During the heat treatment in step S30, the binder and conductive material in the active material layer become CO2 and H2O, which are vaporized and removed. During this process, CO2 and H2O may react with the lithium on the surface of the active material to form Li2CO3 or LiOH, or fluorine (F) present in the binder such as PVdF may react with the metal elements that constitute the positive electrode active material to form LiF or metal fluorides. If LiF or metal fluorides remain, the battery characteristics will deteriorate when the active material is reused. In the present invention, step S40 of primary cleaning with an aqueous solution of a basic lithium compound is added to remove reactants that may be generated on the surface of the reused active material in the heat treatment step S30, thereby preventing foreign matter from remaining on the surface of the recycled active material.
[0063] In step S40, it is important to wash with an aqueous solution of a lithium compound that is basic in an aqueous solution. If an aqueous solution of sulfuric acid or hydrochloric acid is used instead of an aqueous solution of a lithium compound that is basic in an aqueous solution, F on the surface of the active material can be washed away, but transition metals (Co, Mg) present in the active material will be eluted, lowering the performance of the reused positive electrode active material. The aqueous solution of a lithium compound that is basic in an aqueous solution used in the present invention is highly preferable because it can not only remove the binder that may remain even in trace amounts after the thermal decomposition in step S30, but also plays a role in compensating for the amount of lithium that may be eluted during the washing process without eluting transition metals present in the active material.
[0064] In the present invention, in step S40, the LiF content on the surface of the recovered active material can be adjusted to less than 500 ppm, which can improve the capacity. Preferably, the F content can be 100 ppm or less. More preferably, the F content can be 30 ppm or less.
[0065] Next, a lithium precursor is added to the primarily washed active material, and annealing is performed (step S50).
[0066] Lithium loss may occur in the active material during the previous steps S30 and S40, and step S50 replenishes such lithium loss.
[0067] Moreover, in step S50, the crystal structure of the active material is restored by annealing, so that the properties of the reused active material are restored or improved to the level of a fresh active material that has never been used (unused).
[0068] During the previous steps S30 and S40, a deformed structure may appear on the surface of the active material. For example, in the active material that is an NCM-based lithium transition metal composite oxide, Ni may be converted into rock salt [NiCO3·2Ni(OH)2·H2O] by moisture in step S40 to form a spinel structure. If a battery is manufactured in this state, there is a risk of deterioration of battery characteristics such as a decrease in capacity. In the present invention, the crystal structure is restored in step S50. For example, the active material that is an NCM-based lithium transition metal composite oxide is restored to a hexagonal crystal structure again. This makes it possible to restore or improve the initial characteristics to a level similar to that of a fresh active material.
[0069] The lithium precursor in step S50 may be any one or more of LiOH, Li2CO3, LiNO3, and Li2O.
[0070] The method of adding the lithium precursor to the first washed active material may be to add the lithium precursor in a solid or liquid phase after drying the washed active material. As another example, a lithium precursor solution may be added to the washed active material and spray-dried, so that the drying and addition of the lithium precursor may be performed in one step. The lithium precursor solution may be a lithium compound that is soluble in an aqueous solution or an organic solvent.
[0071] If the active material particles are dried immediately in an oven after the surface modification process by the first cleaning, the particles may aggregate and form lumps. In order to mix the lithium precursor with the aggregated particles, grinding of the lumps may be required, and in order to mix the solid-phase lithium precursor, powder mixing or milling processes must be performed when mixing the materials, which may make the process complicated and make continuous processes difficult. In addition, particularly in the case of NCM-based positive electrode active materials, if powder mixing or milling with the lithium precursor is performed in the presence of moisture, the positive electrode active material absorbs moisture and causes severe aggregation. Therefore, if the active material is mixed with a lithium precursor solution after the first cleaning, dispersed, and spray-dried, the particle aggregation due to drying and the trouble of mixing the solid-phase lithium precursor can be eliminated. In other words, spray drying can have the advantage of producing the product in powder form rather than as a lump.
[0072] In spray drying, the lithium precursor solution is dried immediately after spraying, and the lithium precursor components are coated or contacted with the surface of the active material. At this time, when the lithium precursor solution as a solvent dries, the particles aggregate due to capillary force, which has the advantage of adjusting the particle size. In the case of cathode scraps made from electrodes, the surface particles may be pressed during the rolling process, causing cracks or breakage. In particular, NCM-based active materials have a problem that the particles are more likely to break due to rolling during the formation of the electrode compared to LCO, so there are more small particles in the recovered active material compared to fresh active materials, and the particles are non-uniform.
[0073] In addition, NCM-based active materials include large particles that are formed by the aggregation of primary particles having a size of several tens to several hundreds of nm, and a positive electrode made from such an active material may have secondary particles that are broken into primary particles or smaller particles that are larger than the large particles during rolling to adjust the porosity in the electrode. The more particles that are broken by rolling, the greater the specific surface area of the active material, so that reused active materials obtained from rolled electrodes may have problems that affect the slurry properties, electrode adhesive strength, and electrode performance when reused.
[0074] In order for the active material to reach a level where it can be reused, it is preferable that the particle size distribution does not differ from that of fresh active material. The spray drying proposed in this embodiment can solidify small particles that are broken during rolling and restore them to large particles, eliminating particle non-uniformity (variation) and making the particle size closer to the initial characteristics of the fresh active material. This effect is particularly prominent in NCM-based active materials, which suffer from severe particle cracking during the previous rolling process. Therefore, it is expected that the battery characteristics obtained by reusing the active material recovered by the method of the present invention will be comparable to those obtained by using fresh active material.
[0075] As explained above, through the spray drying step, the surface of the active material is coated with the lithium precursor, and the active material is obtained by adjusting the particles. The addition of the lithium precursor, granulation, and drying are performed in one step, which has the effect of simplifying the process. In addition, spray drying is unique in that it is not just a means to obtain an active material, but a means to re-granulate particles that have been used and broken by rolling, etc.
[0076] In addition, since the active material particles washed in the previous step are mixed and dispersed in a lithium precursor solution of a predetermined concentration, washing and spray drying can be performed continuously. Thus, the method for reusing an active material according to the present embodiment has the advantage that the steps are continuous, and lithium precursor coating, drying, and granulation (particle reconditioning) are performed simultaneously in one step.
[0077] The lithium precursor is added in an amount that can compensate for the ratio of lithium to other metals in the raw active material (i.e., fresh active material) used in the active material layer. For example, when the ratio of lithium to other metals in the fresh active material is 1, the lithium precursor can be added so that the lithium addition amount is 0.001 to 0.4 molar ratio. Desirably, the lithium precursor is added so that the lithium addition amount is 0.01 to 0.2 molar ratio. Addition of an excessive amount of lithium precursor other than the amount of lithium lost by cleaning or the like leaves unreacted lithium precursor in the reused active material, which is a factor of increasing resistance during the reuse process of the active material, so it is necessary to administer (add) an appropriate amount of lithium precursor.
[0078] Preferably, the lithium precursor can be added so that the amount of lithium added is 0.0001 to 0.1 molar ratio based on the molar ratio of lithium:other metal=1:1. The reason for adding an excess amount of lithium in this way is to form a surface protective layer by surface coating on the active material, which will be further explained below. When a secondary battery is manufactured from such an active material, it is possible to maintain the life characteristics while suppressing side reactions caused by the electrolyte.
[0079] The annealing can be performed in air or oxygen atmosphere at 400 to 1000°C. When reusing a high-content Ni-based positive electrode active material, it is preferable to perform the annealing in an oxygen atmosphere for Ni stability. O2 with a purity of 80% or more, preferably 90% or more, may be used.
[0080] The annealing temperature may be 600 to 900°C. This temperature must vary within a limited range depending on the type of lithium precursor. The annealing time should be 1 hour or more. It is preferably around 5 hours. If the annealing time is long, the crystal structure can be sufficiently restored, but even if annealing is performed for a long time, the performance is not significantly affected. The annealing time is, for example, within 15 hours. The annealing device may be the same as or similar to the device in the heat treatment step S30.
[0081] For example, when Li2CO3 is used as the lithium precursor, the annealing temperature is preferably 700 to 900°C, more preferably 710 to 780°C. This is because the melting point of Li2CO3 is 723°C. Most preferably, it is 750°C. When LiOH is used as the lithium precursor, the annealing temperature is preferably 400 to 600°C, more preferably 450 to 480°C. This is because the melting point of LiOH is 462°C.
[0082] The annealing temperature is preferably above the melting point of the lithium precursor, but should not exceed 1000° C., as this will cause thermal decomposition of the cathode active material, resulting in a loss of performance of the active material.
[0083] Next, the annealed active material is subjected to a second cleaning (step S60).
[0084] After the lithium precursor is added in step S50, the lithium precursor that has not been involved in the reaction is present on the surface of the active material in the form of LiOH and Li2CO3, so a residual lithium removal step is necessary to remove the lithium precursor. The secondary cleaning can preferably be performed using water (distilled water). In particular, in a high-content Ni-based positive electrode active material, as the Ni content increases, lithium impurities, especially lithium carbonate (Li2CO3) impurities, tend to remain on the surface, and such impurities may react with the electrolyte to reduce the performance of the battery and generate gas, so strict management is desired. The secondary cleaning step of the present invention is effective in removing residual lithium compounds, and is therefore particularly suitable for the method of reusing a high-content Ni-based positive electrode active material.
[0085] Next, the surface of the second washed active material is coated (step S70). After the washed active material is dried, a final surface coating is performed to recover the capacity of the reused active material. By performing step S70, a reusable active material can be obtained.
[0086] The surface coating step may be performed by coating the surface with at least one of metal, organometallic, and carbon components in a solid or liquid phase manner, followed by heat treatment at 100 to 1200°C. If heat treatment is performed at a temperature exceeding 1200°C, performance may be reduced due to thermal decomposition of the positive electrode active material. In the surface coating, methods such as mixing, milling, spray drying, and grinding may be used to coat the surface in a solid or liquid phase manner.
[0087] A surface protective layer made of a different metal is formed by the surface coating. When the molar ratio of lithium to other metals in the positive electrode active material is 1:1, if the lithium in the active material reacts with the surface coating material and the molar ratio of lithium to other metals in the positive electrode active material falls below 1:1, the capacity cannot be expressed at 100%. Therefore, not only is the lithium that is insufficient in the previous step S50 added so that the molar ratio of lithium to other metals in the positive electrode active material becomes 1:1, but also an excess amount is added so that lithium is further contained in the positive electrode active material in a molar ratio of 0.0001 to 0.1 relative to the other metals. In this way, a surface protective layer can be formed even when the molar ratio of lithium to other metals in the positive electrode active material becomes 1:1 during the surface coating.
[0088] Specifically, when the active material is coated with metal oxides such as B, W, and B-W, and then heat-treated, a lithium borooxide layer can be formed on the surface of the active material, which acts as a surface protection layer. The lithium further added in step S50 at a molar ratio of 0.0001 to 0.1 reacts with the metal oxides such as B, W, and B-W in step S70, and the molar ratio of lithium to other metals in the positive electrode active material does not decrease below 1:1, so that no capacity loss occurs.
[0089] The reusable active material may have an F content of 100 ppm or less. According to the present invention, it is possible to recover an active material with a reduced F content, and when this active material is reused as an active material, excellent resistance and capacity characteristics can be achieved.
[0090] Thus, according to the present invention, LiF or metal fluoride is removed in step S40 of the first cleaning. The cleaning and drying steps using an aqueous solution of a lithium compound that is alkaline in aqueous solution state are safe and inexpensive, and can remove LiF or metal fluoride without loss of other elements, and can prevent the elution of transition metals, etc., and can replenish lithium loss that occurs during the process. The annealing step in step S50 is also safe and inexpensive, and has the advantage of recovering the crystal structure, i.e., improving the crystallinity, to recover the battery characteristics of the reused active material. The secondary cleaning step S60 can remove residual lithium remaining on the surface after adding the lithium precursor. The surface coating step S70 can provide a reused active material at a level equal to or similar to that of a fresh active material.
[0091] The reusable active material obtained by the present invention may have a particle size distribution similar to that of a fresh active material, and may not require a separate treatment to adjust the particle size distribution. Since the carbon components generated by carbonization of the binder or conductive material do not remain on the surface, a step of removing such carbon components is not required. In addition, the present invention can be effectively applied to a method for reusing a high-content Ni-based positive electrode active material, and the characteristics of the reused active material can be restored or improved to a level of 99% or more compared to a fresh active material that has never been used. Therefore, the active material obtained by the method of FIG. 2 above may be reused as it is without a separate treatment and used to manufacture a positive electrode.
[0092] The method according to the present invention is very suitable for the reuse of NCM-based, NCA-based, and NCMA-based lithium composite transition metal oxide active materials. The reused active material obtained by the present invention may be used 100% as it is without adjusting the composition, or may be mixed with fresh active material, and mixed with a conductive material, a binder, and a solvent to prepare a slurry and use it.
[0093] Experimental examples of the present invention will now be described in detail.
[0094] <Experimental Example> Positive electrode active material samples were prepared under the following conditions and by the following method.
[0095] Sample 1: A fresh active material of NCM-based lithium composite transition metal oxide.
[0096] Sample 2: This is a positive electrode active material that was subjected to steps S10, S20, and S30 according to the method for reusing a positive electrode active material of the present invention, and was desorbed in the process of removing the binder and conductive material and separating the current collector. The heat treatment in step S30 was performed under the conditions of 550°C / 0.5 hours, increasing speed of 5°C / min, and air 3L / min.
[0097] Sample 3: This is an active material obtained by subjecting Sample 2 to step S40 according to the method for reusing a positive electrode active material of the present invention and completing the primary cleaning. The primary cleaning was performed twice. The first cleaning was performed by stirring at 300 rpm / 10 minutes with a ratio of active material:cleaning solution = 1:30, and then extracting only the active material with a reduced pressure filter. It was again washed with a ratio of active material:cleaning solution = 1:10. The primary cleaning was performed to remove LiF remaining on the surface of the active material.
[0098] Sample 4 (corresponding to an embodiment of the present invention in which all steps of the method of the present invention were performed): Sample 3 was dried, and 0.11 mol of LiOH, a lithium precursor, was added, and annealing was performed at 750°C / 5 hours and O2 was supplied at 3L / min, in step S50 of the method of reusing the positive electrode active material of the present invention. Then, S60, which is a water washing step to remove surface residual lithium, was performed. The water washing was performed with active material: water washing solution = 1:1, stirring at 300 rpm / 1 minute, followed by vacuum drying overnight after reduced pressure filtering (130°C drying). Then, in order to add boron, 1000 ppm H3BO3 was added, and step S70 was performed in which coating was performed at 300°C / 5 hours, with an increase rate of 2°C / min and air 3L / min.
[0099] Sample 5 (corresponding to an example of the present invention): A positive electrode active material was recovered in the same manner as in Sample 4. However, the amount of lithium precursor added in step S50 was increased to 0.13 mol.
[0100] Sample 6 (corresponding to an example of the present invention): A positive electrode active material was recovered in the same manner as in Sample 4. However, the amount of lithium precursor added in step S50 was increased to 0.15 mol.
[0101] Sample 7 (corresponding to an example of the present invention): A positive electrode active material was recovered in the same manner as in Sample 4. However, the amount of lithium precursor added in step S50 was increased to 0.17 mol.
[0102] Sample 8 (corresponding to a comparative example in which the secondary cleaning step of the present invention is not performed): Sample 3 was dried, and 0.11 mol of LiOH, a lithium precursor, was added, and annealing was performed at 750° C. / 5 hours with O2 supplied at 3 L / min in step S50 of the method for reusing a positive electrode active material of the present invention. Thereafter, step S70 was performed similarly to sample 4 without performing the secondary cleaning step, i.e., without performing step S60.
[0103] Sample 9 (corresponding to a comparative example): A positive electrode active material was recovered in the same manner as in Sample 8. However, the amount of the lithium precursor added in step S50 was 0.13 mol.
[0104] Sample 10 (corresponding to a comparative example): A positive electrode active material was recovered in the same manner as in Sample 8. However, the amount of the lithium precursor added in step S50 was set to 0.15 mol.
[0105] The sample was subjected to ICP analysis to analyze the remaining amount of LiF, the ratio of lithium to other metals in the active material, and the amount of B. Scanning Electron Microscope (SEM) images and particle size were confirmed. In addition, 96.25 wt% of the positive electrode active material, 1.5 wt% of carbon black as a conductive material, and 2.25 wt% of PVdF as a binder were weighed and mixed with NMP to prepare a slurry, and a positive electrode was manufactured, and then a cell (Coin Half Cell: Coin Half Cell, CHC) was manufactured and the electrochemical performance was evaluated.
[0106] Figures 3 and 4 are SEM photographs of Sample 1 and Sample 3. The SEM photographs were taken with a common SEM device commonly used in laboratories. For example, HITACHI's S-4200 may be used for the photographs. However, there is no deviation due to the measurement device or method.
[0107] FIG. 3 is an SEM photograph of fresh active material of Sample 1. FIG. 4 is an SEM photograph of Sample 3. Comparing FIG. 4 with FIG. 3, the active material of FIG. 4 has been broken down into smaller particles. Sample 3 is an active material that has been subjected to step S40 of the method for reusing a positive electrode active material of the present invention up to cleaning. It can be seen that the active material is broken down into smaller particles after cleaning. The broken particles are in contact with or dispersed by larger particles.
[0108] For Sample 1, Sample 2, and Sample 3, the ratio of lithium / other metals in the active material (Li / Metal Ratio), F content (unit: mg / kg), and B content (unit: mg / kg) were detected and analyzed by ICP, and the results are shown in Table 1 below.
[0109] [Table 1]
[0110] Referring to Table 1, the lithium / other metal ratio of sample 1 is 1.01, but when the heat treatment in step S30 is performed as in sample 2, the ratio decreases to 0.99, and when the first cleaning in step S40 is performed as in sample 3, the ratio further decreases to 0.9. In other words, it can be seen that lithium is lost through steps such as heat treatment and cleaning, and therefore insufficient lithium must be replenished.
[0111] Table 1 shows values measured by ICP analysis, and as mentioned above, ICP analysis has an error of about ±0.02. Therefore, even in Comparative Example 1, which is a fresh active material, the ratio of lithium to other metals is not 1:1. Therefore, the amount of lithium precursor added to compensate for the lost lithium is added based on the ratio of lithium to other metals (molar ratio by ICP analysis) in the raw active material (i.e., fresh active material) used in the active material layer.
[0112] Meanwhile, it can be seen that the F content of sample 1 is less than 10 mg / kg, and the F content of sample 2 is much higher than that. This is because LiF is generated during the heat treatment in step S30. Sample 3 further includes a first cleaning step compared to sample 2, and referring to Table 1, it can be seen that the F content in the recovered positive electrode active material of sample 3 is significantly lower than that of sample 2. That is, it can be seen that LiF is dissolved and removed in the lithium compound aqueous solution, which is the cleaning solution, by the first cleaning. Therefore, it can be seen that the removal of LiF is excellent by step S40 of the method proposed in the present invention.
[0113] As can be seen from Sample 1, the fresh active material used in this experiment further contained 1005 mg / kg of B. Referring to Sample 2 in Table 1, it can be seen that the B content decreased compared to Sample 1 through heat treatment, and further decreased in Sample 3 after the first cleaning. Therefore, it can be seen that in order to obtain a reusable active material at the level of the fresh active material, the deficiency of B must be compensated for.
[0114] In this way, depending on the type of active material used initially, a specific element (B in this experiment) may be partially lost during the process of obtaining the reused active material, and in particular, it may be completely removed or only a small amount may remain during the surface modification process by washing, making it difficult to fully recover the characteristics. In this case, it is preferable to perform the surface coating step proposed in the present invention. In this experimental example, the surface coating step is to coat B. The surface coating can function as a surface protective layer for the positive electrode active material. The surface coating can be a process of reconstructing the surface protective layer of the fresh active material while supplementing the specific element that is insufficient. In the case of the fresh active material used in this experiment, the surface protective layer is B, and the amount of lithium lost during the process is interpreted as the ratio of the lithium of the active material itself and other metals is not 1:1 (lithium of the active material itself + lithium forming the surface protective layer): other metals.
[0115] FIG. 5 and FIG. 6 are particle size distribution graphs of the active materials of Sample 1 and Samples 3 to 6. The particle size distribution can be obtained by a general particle size analyzer commonly used in laboratories. For example, it can be measured using a Horiba LA 950V2 particle size analyzer. However, there is no deviation due to the measurement device or method. In FIG. 5 and FIG. 6, the horizontal axis represents particle size (μm) and the vertical axis represents volume %. Table 2 shows D5, D50 and D95 of the particle size distribution in FIG. 5, and Table 3 shows D5, D50 and D95 of the particle size distribution in FIG. 6 (unit: μm). (D* indicates the particle diameter at the point where the distribution rate of a certain particle is *%)
[0116] [Table 2]
[0117] [Table 3]
[0118] The particle size distribution graph in FIG. 5 is consistent with the SEM results in FIG. 3 and FIG. 4. Since the NCM-based active material has large particle cracks due to rolling during electrode formation, it can be seen that the particle size distribution of Sample 3 after heat treatment and cleaning shows that many small particles are formed compared to Sample 1. Also, referring to FIG. 6, in Samples 4 to 6 (corresponding to the examples of the present invention) that were annealed, the particle aggregation phenomenon increases, and the particle size distribution is similar to that of Sample 1. Thus, according to the present invention, since the particle size distribution of the reusable active material is the same as that of a fresh active material, the initial characteristics are almost maintained, and it is expected that the battery characteristics of the battery using this reusable active material will be at a similar level to that of a battery using a fresh active material.
[0119] Figures 7 and 8 show the results of cell evaluation using sample active materials. The capacity was evaluated according to the number of cycles repeated at different currents to examine the rate performance. The equipment used for the evaluation was a typical charge / discharge experimental equipment commonly used in laboratories. There was no deviation due to the measurement equipment or method. In the graphs of Figures 7 and 8, the horizontal axis represents the number of cycles and the vertical axis represents the capacity.
[0120] The voltage was set to 3 to 4.3 V, and charging and discharging was performed at 0.1 C / 0.1 C-0.33 C / 0.33 C-0.5 C / 0.1 C-0.5 C / 1 C-0.5 C / 2 C. The electrolyte that constitutes the cell was a carbonate-based electrolyte, with ethylene carbonate (EC): ethyl methyl carbonate (EMC) = 3:7, and contained some additives.
[0121] First, Fig. 7 shows a comparison between Sample 1, which is a fresh active material, and Samples 4 to 7, which are examples of the present invention. Table 4 shows the charge capacity, discharge capacity, and efficiency of these samples.
[0122] [Table 4]
[0123] 7 and Table 4, when the lithium precursor was added according to the embodiment of the present invention, and the surface residual lithium precursor was also removed by secondary cleaning after annealing, the charge / discharge capacity was the same as that of a fresh active material. When an amount of lithium in excess of 0.11 mol, which was lost during the process, was added, that is, the capacity expression rate was higher in samples 5 to 7 compared to sample 4. It was confirmed that not only the initial capacity but also the C-rate capacity was at a similar level to that of a fresh active material.
[0124] Next, FIG. 8 shows a comparison between Sample 1 and Samples 8 to 10 (corresponding to comparative examples). Samples 8 to 10 were not subjected to a secondary cleaning step after annealing. Table 5 summarizes the charge capacity, discharge capacity, and efficiency.
[0125] [Table 5]
[0126] 8 and Table 5, it can be seen that even if annealing is performed after the addition of the lithium precursor, if the residual lithium precursor on the surface is not removed afterwards, a lower capacity expression rate is observed compared to a fresh active material. There is no difference in the initial capacity when the amount of lithium lost during the process is 0.11 mol and when an excess amount is added, but at high C rates, the capacity increases slightly when an excess amount of lithium is added.
[0127] The amount of remaining lithium was analyzed before and after cleaning of the surface residual lithium precursor. 5 g of each active material was taken from Sample 1, Sample 6, Sample 7, and Sample 10, dispersed in 100 ml distilled water, mixed at 300 rpm for 5 minutes, and then the active material was filtered. The filtered solution was titrated with 0.1 M HCl solution to calculate the pH and the concentration of LiOH and Li2CO3 dissolved from the active material. When an excess amount of LiOH is dissolved in a solvent (NMP) during the electrode manufacturing process, the solvent is made basic. The basic solvent mixes with the binder and gels the slurry, making it impossible to manufacture the electrode. In addition, the excess amount of Li2CO3 is easily attacked by hydrofluoric acid (HF) generated by the very small amount of water molecules present in the electrolyte, and is decomposed to generate gas. Therefore, lithium compounds that provide residual lithium, such as LiOH and Li2CO3, must be removed.
[0128] [Table 6]
[0129] When the surface residual lithium is not removed, as in sample 10, the total residual lithium content is Li 0.823 wt.%, whereas when the surface residual lithium is removed, as in samples 6 and 7 according to the present invention, it can be seen that the residual lithium is controlled at a level similar to that of sample 1.
[0130] In this way, the present invention makes it possible to recover active materials from cathode scraps to a level that allows them to be directly reused. The present invention is safe because it does not use toxic or explosive solvents such as NMP, DMC, acetone, or methanol, and is suitable for mass production because it uses simple and safe methods such as heat treatment, washing and drying, and annealing.
[0131] In addition, according to the present invention, it is possible to reuse cathode scraps using a simple, environmentally friendly, and economical method, and even if the thus-prepared lithium composite transition metal oxide cathode active material is reused as is to manufacture a lithium secondary battery, there is no problem with the performance of the battery. In particular, according to the present invention, it is possible to effectively apply the method for reusing a high-content Ni-based cathode active material by performing a secondary cleaning after annealing, and the characteristics of the reused active material can be restored or improved to a level of 99% or more compared to a fresh active material that has never been used.
[0132] Although the present invention has been described above with reference to limited examples and drawings, the present invention is not limited thereto, and it goes without saying that various modifications and variations are possible within the technical spirit of the present invention and the scope of the claims which will be described later.
Claims
1. a step of heat-treating a cathode scrap including a cathode active material layer of a lithium composite transition metal oxide including nickel, cobalt, and manganese or aluminum on a current collector to thermally decompose a binder and a conductive material in the cathode active material layer, thereby separating the current collector from the cathode active material layer and recovering an active material in the cathode active material layer; a step of first washing the recovered active material with an aqueous solution of a lithium compound that is basic in an aqueous solution state to remove LiF, metal fluoride and binder, and replenishing lithium; adding a lithium precursor to the washed active material and annealing; a second washing step of the annealed active material to remove lithium carbonate; a step of forming a surface protective layer of a different metal on the second washed active material to obtain a reusable active material; A method for reusing a positive electrode active material, comprising:
2. 2. The method for reusing a positive electrode active material according to claim 1, wherein the heat treatment is carried out in air or an oxygen atmosphere at 300 to 650° C.
3. 2. The method of claim 1, wherein the lithium compound aqueous solution contains more than 0% and not more than 15% of a lithium compound, and the first cleaning is performed within one hour.
4. The method for reusing a positive electrode active material according to claim 1 , wherein the primary washing is performed by immersing the recovered active material in the aqueous lithium compound solution while stirring the aqueous lithium compound solution.
5. The lithium precursors used for the annealing were LiOH, Li 2 CO 3 , LiNO 3 and Li 2 The method for reusing a positive electrode active material according to claim 1 , wherein the positive electrode active material is any one or more of O.
6. 2. The method for reusing a positive electrode active material according to claim 1, wherein the lithium precursor is added in an amount sufficient to compensate for a ratio of lost lithium relative to a ratio of lithium and other metals in a raw active material used for the positive electrode active material layer.
7. The method for reusing a positive electrode active material according to claim 6, wherein the lithium precursor is added so that the amount of lithium added is 0.001 to 0.4 molar ratio.
8. The method for reusing a positive electrode active material according to claim 6, wherein the lithium precursor is added so that the amount of lithium further added is 0.0001 to 0.1 molar ratio based on a molar ratio of lithium:other metal=1:
1.
9. The method for reusing a positive electrode active material according to claim 1, wherein the annealing is performed in air or an oxygen atmosphere at 400 to 1000° C.
10. The method of claim 1 , wherein the temperature in the annealing step is a temperature exceeding the melting point of the lithium precursor.
11. 2. The method for reusing a positive electrode active material according to claim 1, wherein the active material in the positive electrode active material layer is recovered in a powder form, and no carbon component resulting from carbonization of the binder or conductive material remains on the surface.
12. 2. The method of claim 1, wherein the surface-coating step comprises coating the surface with at least one of a metal, an organometallic, and a carbon component in a solid or liquid phase manner, and then heat-treating the surface at 100 to 1200° C.
13. 2. The method for reusing a positive electrode active material according to claim 1, wherein the content of the nickel is 60 mol % or more based on the total number of moles of the transition metals.
14. 2. The method for reusing a positive electrode active material according to claim 1, wherein the reusable active material has a fluorine (F) content of 100 ppm or less.
15. The method for reusing a positive electrode active material according to claim 1 , further comprising, after the step of primarily washing, mixing the primarily washed active material with a lithium precursor solution and spray-drying the mixture.
Citation Information
Patent Citations
Method for recovering leftover materials of lithium ion battery cathodes
CN105870533A
Lithium battery material recovery method
JP1994251805A
Method for recovering lithium
JP2013095951A
Positive electrode active material recovery method
JP2015185471A
Method for regenerating lithium composite oxide, lithium composite oxide, electrochemical device, and lithium ion secondary battery
JP2016085953A